Alfie : (the turtle that disappeared) - Heder, Thyra (Abrams Books for Young Readers, 2017)
Told from the perspective of both the girl, Nia, and her pet turtle, Alfie, and describes what happens when he disappears on the eve of her seventh birthday to find her a special present.